Psychomotor symptomatology in psychiatric illnesses - Manuel Morrens (Frontiers Research Topics, 2015)
Psychomotor symptoms are those symptoms that are characterized by deficits in the initiation, execution and monitoring of movements, such as psychomotor slowing, catatonia, neurological soft signs (NSS), reduction in motor activity or extrapyramidal symptoms (EPS). These symptoms have not always received the attention they deserve although they can be observed in a wide range of psychiatric illnesses, including mood disorders, psychotic disorders, anxiety disorders, pervasive developmental disorders and personality disorders. Nevertheless, these symptoms seem to have prognostic value on clinical and functional outcome in several pathologies. In the late 19th century, the founding fathers of modern psychiatry (including Kahlbaum, Wernicke, Kraepelin and Bleuler) had a strong focus on psychomotor abnormalities in their description and definitions of psychiatric illnesses and systematically recognized these as core features of several psychiatric pathologies. Nevertheless, emphasis on these symptoms has reduced substantially since the emergence of psychopharmacology, given the association between antipsychotics or antidepressants and medication-induced motor deficits. This has resulted in the general idea that most if not all psychomotor deficits were merely side effects of their treatment rather than intrinsic features of the illness. Yet, the last two decades a renewed interest in these deficits can be observed and has yielded an exponential growth of research into these psychomotor symptoms in several psychiatric illnesses. This recent evolution is also reflected in the increased appreciation of these symptoms in the DSM-5. As a result of this increased focus, new insights into the clinical and demographical presentation, the etiology, the course, the prognostic value as well as treatment aspects of psychomotor symptomatology in different illnesses has emerged. Still, many new questions arise from these findings. This research topic is comprised of all types of contributions (original research, reviews, and opinion piece) with a focus on psychomotor symptomatology in a psychiatric illness, especially research focusing on one or more of the following topics: the clinical presentation of the psychomotor syndrome; the course through the illness; the diagnostical specificity of the syndrome; the underlying neurobiological or neuropsychological processes; new assessment techniques; pharmacological or non-pharmacological treatment strategies.